Effect of free medicine distribution on ability to make ends meet: post hoc quantitative subgroup analysis and qualitative thematic analysis - Nav Persaud; Hannah Woods; Ri Wang; Aine Workentin; Margaret Hess (BMJ Open)
Objectives Out-of-pocket medication costs can contribute to financial insecurity and many Canadians have trouble affording medicines. This study aimed to determine if the effect of eliminating out-of-pocket medication costs on individual’s financial security varied by gender, racialisation, income and location.Design In this post hoc subgroup analysis of the CLEAN Meds trial, a binary logistic regression model was fitted and a qualitative inductive thematic analysis of comments related to participant’s ability to make ends meet was carried out.Setting Primary care patients in Ontario, Canada.Participants Adult patients (786) who reported not being able to afford medicines during the previous 12 months.Intervention Free access to a comprehensive list of essential medicines for 24 months.Primary outcome measure Ability to make ends meet or afford basic necessities.Results There were no significant differences in the effect of free medicine distribution by gender (OR for male 0.82; 95% CI 0.51 to 1.33, p=0.76), age (older than 65 years OR 1.28; 95 % CI 0.62 to 2.64, p=0.73), racialisation (OR 0.85; 95 % CI 0.51 to 1.45, p=0.66), household income level (above US$30 000 per year OR 1.08; 95 % CI 0.64 to 1.80, p=0.99) or location (urban OR 0.47; 95 % CI 0.23 to 0.96, p=0.10). The main theme in the qualitative analysis was insufficient income, and there were three related themes: out-of-pocket medication expenses, cost-related non-adherence and the importance of medication coverage. In the intervention group, additional themes identified included improved health, functioning and access to basic needs.Conclusions Providing free essential medications improved financial security across subgroups in a trial population who all had trouble affording medicines. Free access to medicines could improve health directly by improving medicine adherence and indirectly by making other necessities more accessible to people who have an insufficient income.Trial registration number NCT02744963.